Geographic and research center origins of rice resistance to Asian planthoppers and leafhoppers: implications for rice breeding and gene deployment - Horgan, Finbarr G.; Srinivasan, Thanga; Bentur, Jagadish; Kumar, Ram; Bhanu, K.; Sarao, Preetinder; Chien, Ho; Almazan, Maria; Bernal, Carmencita; Ramal, Angelee; Ferrater, Jedeliza; Huang, Shou-Horng (MDPI, 2017)
This study examines aspects of virulence to resistant rice varieties among planthoppers and leafhoppers. Using a series of resistant varieties, brown planthopper, Nilaparvata lugens, virulence was assessed in seedlings and early-tillering plants at seven research centers in South and East Asia. Virulence of the whitebacked planthopper, Sogatella furcifera, in Taiwan and the Philippines was also assessed. Phylogenetic analysis of the varieties using single-nucleotide polymorphisms (SNPs) indicated a clade of highly resistant varieties from South Asia with two further South Asian clades of moderate resistance. Greenhouse bioassays indicated that planthoppers can develop virulence against multiple resistance genes including genes introgressed from wild rice species. Nilaparvata lugens populations from Punjab (India) and the Mekong Delta (Vietnam) were highly virulent to a range of key resistance donors irrespective of variety origin. Sogatella furcifera populations were less virulent to donors than N. lugens; however, several genes for resistance to S. furcifera are now ineffective in East Asia. A clade of International Rice Research Institute (IRRI)-bred varieties and breeding lines, without identified leafhopper-resistance genes, were highly resistant to the green leafhopper, Nephotettix virescens. Routine phenotyping during breeding programs likely maintains high levels of quantitative resistance to leafhoppers. We discuss these results in the light of breeding and deploying resistant rice in Asia.